2017
DOI: 10.1371/journal.pone.0181221
|View full text |Cite
|
Sign up to set email alerts
|

Reduced susceptibility of clinical strains of Mycobacterium tuberculosis to reactive nitrogen species promotes survival in activated macrophages

Abstract: BackgroundDrugs such as isoniazid (INH) and pretomanid (PRT), used against Mycobacterium tuberculosis are active partly through generation of reactive nitrogen species (RNS). The aim of this study was to explore variability in intracellular susceptibility to nitric oxide (NO) in clinical strains of M. tuberculosis.MethodLuciferase-expressing clinical M. tuberculosis strains with or without INH resistance were exposed to RNS donors (DETA/NO and SIN-1) in broth cultures and bacterial survival was analysed by lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…There is a precedence that mycobacteria primed by exposure to oxidative stress have enhanced survival in the host [ 65 , 66 ]. This is, in part, due to two well described virulence factors, catalase (KatG) and alkylhydroperoxide reductase (AhpC), critical elements of the antioxidant defense system, whose expression is induced by oxidative stress and correlates with enhanced survival and hypervirulence in animal models [ 34 , 44 , 45 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a precedence that mycobacteria primed by exposure to oxidative stress have enhanced survival in the host [ 65 , 66 ]. This is, in part, due to two well described virulence factors, catalase (KatG) and alkylhydroperoxide reductase (AhpC), critical elements of the antioxidant defense system, whose expression is induced by oxidative stress and correlates with enhanced survival and hypervirulence in animal models [ 34 , 44 , 45 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased mycobacterial NADH/NAD + ratio, through mutation of ndh, which encodes a type II NADH dehydrogenase, exhibits co-resistance to isoniazid and ethionamide [95]. Mtb strains that show resistance to isoniazid also exhibit more resistance to ROS compared to the wild-type Mtb (CDC1551 and CB3.3) strains [96,97]. It has also been observed that these strains have increased resistance to peroxide and acidified nitrite molecules [96,98].…”
Section: Oxidative Stress and Tbmentioning
confidence: 99%
“…Mechanistically, among all the ROS, nitric oxide (NO) is known to be one of the major contributors as an anti-TB agent. NO is synthesized by NO synthase in macrophages, and NO synthase-deficient mice have been shown to exhibit increased susceptibility to M. tuberculosis [ 36 ]. Patients with active pulmonary TB have higher levels of NO in their lungs [ 36 ].…”
Section: Oxidative Stress Response Against Mycobacteriummentioning
confidence: 99%
“…NO is synthesized by NO synthase in macrophages, and NO synthase-deficient mice have been shown to exhibit increased susceptibility to M. tuberculosis [ 36 ]. Patients with active pulmonary TB have higher levels of NO in their lungs [ 36 ]. The accumulation of ROS during OS can further produce superoxide, hydrogen peroxide, and hydroxyl radicals via single-electron reduction chain reactions [ 32 ].…”
Section: Oxidative Stress Response Against Mycobacteriummentioning
confidence: 99%
See 1 more Smart Citation